Durable response to hormonal therapy in a patient with rapidly progressive low-grade serous ovarian cancer: A case report - Catherine H. Watson; Angeles Alvarez Secord (Elsevier, 2020)
This case report describes a 46-year-old patient with rapidly progressive stage IIIA1 estrogen receptor positive low grade serous ovarian cancer (LGSC). She was optimally debulked with no residual disease and received three cycles of adjuvant liposomal doxorubicin and carboplatin intravenous chemotherapy. CT scan and pelvic exam after her third cycle revealed a 5.7 cm nodular fixed left vaginal cuff mass involving the rectosigmoid consistent with rapidly progressive disease on chemotherapy. The decision was made to initiate letrozole, and she demonstrated a prolonged partial response for 34 months on hormonal therapy. The optimal management of newly diagnosed LGSC has yet to be determined. This unique case suggests that patients with newly diagnosed disease will not be compromised if treated with adjuvant hormonal monotherapy.